LEGAL IMPLICATIONS OF THE IMPLEMENTATION OF ARTICLE 2 OF LAW NUMBER 1 OF 2023 ON THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Zulkarnain Pasaribu; T. Riza Zarzani; Henry Aspan (PT. Sinergi Legal Publisher, 2025)
The implementation of Article 2 of Law Number 1 of 2023 concerning the Criminal Code (KUHP) marks a significant change in the national legal landscape by formally recognizing the living law in society, including customary law, as the basis for sentencing. This article represents a shift from the principle of formal legality, which primarily recognizes written law, to the principle of material legality that is more inclusive of local norms and values ​​in the criminal justice system. The recognition of customary law in the Criminal Code demonstrates the integration of local wisdom into the national legal framework, ensuring that justice is upheld in a manner that is appropriate to the diverse social and cultural realities of Indonesian society. However, the incorporation of customary law into the national legal system presents challenges in harmonizing it with universally recognized principles of justice and human rights. This study examines the legal implications of the implementation of Article 2 on the criminal justice system, focusing on its impact on law enforcement, prosecution, and decision-making in court. This study also explores potential conflicts between customary law and national law, especially regarding consistency in law enforcement and protection of human rights. This study highlights the need for careful integration of customary law to maintain legal certainty and justice, while respecting Indonesia's cultural diversity. The findings of this study are expected to provide constructive recommendations for policymakers and legal practitioners in managing the application of customary law in the criminal justice system in Indonesia.